Biomedical Engineering Professional Skills Development: The RADxSM Tech Impact on Graduates and Faculty - Andrew DiMeo; Chipo Afamefuna; Skyler Ward; Phil Weilerstein; Elias Caro; Max Germer; Alexander Carroll (IEEE Open Journal of Engineering in Medicine and Biology, 2021)
There are many benefits of the RADxSM Tech initiative worth exploring beyond that of the current acceleration of diagnostic tests being developed and deployed to the nation. One of those benefits has been the impact on work readiness for recent biomedical engineering (BME) graduates who have been hired by RADx Tech as Assistant Project Facilitators (APFs) and to the students and faculty members on applicant teams. This paper includes a literature review of the current status of BME professional skills development in traditional academic and clinical settings. The organizational structure of RADx Tech teams is described, including how recent BME graduates are integral to the process. Opportunities are discussed on how the RADx Tech structural model can be leveraged to improve professional skills education. It is concluded that the RADx Tech organizational structure and process including APFs may be replicable. Further research is planned to explore its impact.